Is Music the Next eBooks? An Antitrust Analysis of Apple’s Conduct in the Music Industry - Klebanow, Alexa (The Columbia Journal of Law & the Arts, 2015)
Over the last twenty years, two waves of technological change have transformed the way people purchase and listen to music. First, digital downloads displaced physical sales of albums. More recently, digital downloads, once the primary way to gain access to digital music, have come to be challenged by streaming services. Apple, a leader in the digital download market with iTunes, has engaged in various strategies to meet the challenge. This Note specifically focuses on two types of conduct: Apple’s pressure on labels to enter into exclusive license agreements, also known as windowing, and Apple’s pressure on the market to abandon streaming options like Spotify’s “freemium” service. This Note conducts an antitrust analysis of windowing in the music industry and also examines the legality of eliminating the advertising-based “free” streaming model. The Note engages in an examination of Section 1 and Section 2 Sherman Act claims against Apple for these exclusionary acts based on parallel exclusion, joint refusal to deal, price maintenance, and monopoly maintenance theories. We believe of greatest concern is the potential elimination of the free advertising based model, which may be a per se violation of the antitrust laws